2022
DOI: 10.7759/cureus.28396
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Presentation of Extrapulmonary Legionella: Rhabdomyolysis-Induced Acute Renal Failure and Cerebellar Dysfunction

Abstract: Legionella is most known for causing pneumonia. However, it is a systemic disease that can directly cause severe multi-organ injury in what is sometimes referred to as "extrapulmonary Legionella." In this case report, a reasonably healthy 80-year-old man is found to have Legionella pneumonia complicated by rhabdomyolysis with acute, severe, non-oliguric acute kidney injury, uremic encephalopathy, transaminitis, and cerebellar dysfunction. With a 14-day course of azithromycin and prompt initiation of dialysis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Notably, only one case in the literature with a similar presentation to ours involved renal and neurological dysfunction. Unlike our case, the patient was treated with a 14‐day course of azithromycin and reported improvement in dysarthria and ataxia without complete resolution on a one‐month follow‐up 16 . In a small case series that followed the outcomes of neurological dysfunction of LD patients.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Notably, only one case in the literature with a similar presentation to ours involved renal and neurological dysfunction. Unlike our case, the patient was treated with a 14‐day course of azithromycin and reported improvement in dysarthria and ataxia without complete resolution on a one‐month follow‐up 16 . In a small case series that followed the outcomes of neurological dysfunction of LD patients.…”
Section: Discussionmentioning
confidence: 77%
“…Unlike our case, the patient was treated with a 14-day course of azithromycin and reported improvement in dysarthria and ataxia without complete resolution on a one-month follow-up. 16 In a small case series that followed the outcomes of neurological dysfunction of LD patients. It concluded that out of 17 patients, 12 patients had persistent neurological dysfunction.…”
Section: Discussionmentioning
confidence: 99%